Contribution of Amygdala Histone Acetylation in Early Life Stress-Induced Visceral Hypersensitivity and Emotional Comorbidity - Guan, Le; Shi, Xi; Tang, Ying; Yan, Yan; Chen, Liang; Chen, Yu; Gao, Guangcheng; Lin, Chun; Chen, Aiqin (Frontiers in Neuroscience, 2022)
Patients with irritable bowel syndrome experience not only enhanced visceral pain but also emotional comorbidities, such as anxiety and depression. Early life stress is a high-risk for the development of IBS. Literatures have reported an important epigenetic modulation in sustaining extrinsic phenotypes. The amygdala is closely related to the regulation of visceral functions and emotional experiences. In this study, we hypothesized that ELS-induced reprogramming inappropriate adaptation of histone acetylation modification in the amygdala may result in visceral hypersensitivity and anxiety-like behaviors in ELS rats. To test this hypothesis, the model of ELS rats was established by neonatal colorectal dilatation (CRD). Visceral hypersensitivity was assessed based on the electromyography response of the abdominal external oblique muscle to CRD. Emotional comorbidities were examined using the elevated plus maze test, open field test, and sucrose preference test. Trichostatin A and C646 were microinjected into the central amygdala individually to investigate the effects of different levels of histone acetylation modification on visceral hypersensitivity and emotion. We found neonatal CRD resulted in visceral hypersensitivity and anxiety-like behaviors after adulthood. Inhibiting histone deacetylases (HDACs) in the CeA by TSA enhanced visceral sensitivity but did not affect anxiety-like behaviors, whereas inhibiting HAT by C646 attenuated visceral hypersensitivity in ELS rats. Interestingly, CeA treatment with TSA induced visceral sensitivity and anxiety-like behaviors in the control rats. Western blot showed that the expressions of acetylated 9 residue of Histone 3 (H3K9) and protein kinase C zeta type (PKMζ) were higher in the ELS rats compared to those of the controls. The administration of the PKMζ inhibitor ZIP into the CeA attenuated visceral hypersensitivity of ELS rats. Furthermore, the expression of amygdala PKMζ was enhanced by TSA treatment in control rats. Finally, western blot and immunofluorescence results indicated the decrease of HDAC1 and HDAC2 expressions, but not HDAC3 expression, contributed to the enhancement of histone acetylation in ELS rats. Our results support our hypothesis that amygdala-enhanced histone acetylation induced by stress in early life results in visceral hypersensitivity and anxiety-like behaviors in ELS rats, and reversing the abnormal epigenetic mechanisms may be crucial to relieve chronic symptoms in ELS rats.